Effect of extreme environmental conditions on physical activity patterns pf soccer players - Ozgunen, K.; Kurdak, S.; Cigdem, Z.; Korkmaz, S.; Yazici, Z.; Ersoz, G.; Binnet M. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Soccer teams may sometimes be obliged to play under difficult environmental conditions. Activity patterns of players of different standards have been analyzed by time-motion analysis, but there is dearth of knowledge how the players` match performance is affected by environmental conditions. Purpose: This study aimed to evaluate changes in the activity patterns during a soccer match played in different conditions of environmental temperature and humidity. Methods: Non-acclimatized soccer players (n=10, the goal keeper was excluded, 20 ±2 y, V`O2max=63 ±7 ml/min/kg) played 2 matches in different environmental conditions. Players ingested telemetric core temperature (Tc) sensors prior to each match and wore a heart rate (HR) and global positioning system (GPS) monitor during the match. A computer based analysis program was used to evaluate heart rate and speed changes during the match. The following locomotor categories were used: standing (0 - 0.4 km/h), walking (0.5 - 7.5 km/h), jogging (7.6 - 14.5 km/h), low - moderate running (14.6 - 19.5 km/h), high speed running (19.6 - 25.5 km/h) and sprinting (> 25.6 km/h). These were later divided into five categories: (1) standing; (2) walking; (3) running, encompassing jogging and low - moderate intensity running and (4) high intensity running, consisting of high speed running and sprinting. Results: The average ambient temperature for the June 2007 match was 34 ± 1 °C with a relative humidity of 38 ± 2 %. In the July 2007 match, ambient temperature was recorded as 36 ± 0 °C with a relative humidity of 61 ± 1 %. Peak Tc values recorded for June and July matches were 39.1 ± 0.4 °C, and 39.6 ± 0.3 °C respectively. Total distance covered during June and July matches was 8.6 ± 0.6 and 8.1 ± 0.7 km respectively. The total distance covered in the first and second halves were: 4.4 ± 0.4 and 4.2 ± 0.3 km for June and 4.3 ± 0.5 and 3.8 ± 0.4 km for July matches. The difference between the halves of the July match was significant. The running distance covered in the second half of the July match was significantly shorter than first half of July and second half of June matches (2.1 ± 0.4 and 1.9 ± 0.3 km for the first and second halves of June and 1.9 ± 0.5 and 1.3 ± 0.4 km for the first and second halves of July matches;p<0.05) Conclusion: In soccer matches played in high environmental temperature and humidity, the physical performance of the players may decrease due to high thermal stress. In the present study, the players` increased body core temperature at half time was followed by a decrease in total distance covered in the second half of the game. This may point to a centrally-driven performance reduction.